Immunomodulators in warts: Unexplored or ineffective? - Sinha, Surabhi (Indian J Dermatol, 2015)
Cutaneous warts are known to be recurrent and often resistant to therapy. Resistant warts may reflect a localized or systemic cell mediated immune (CMI) deficiency to HPV. Many modalities of treatment are in use; most of the provider-administered therapies are destructive and cause scarring, such as cryotherapy, chemical cauterisation, curettage, electrodessication and laser removal. Most patient-applied agents like podophyllotoxin have the risk of application-site reactions and recurrence. Thus immunotherapy is a promising modality which could lead to resolution of warts without any physical changes or scarring and in addition would augment the host response against the causative agent, thereby leading to complete resolution and decreased recurrences. Immunomodulators can be administered systemically, intralesionally or intradermally, and topically. A few agents have been tried and studied extensively such as cimetidine and interferons; others are new on the horizon, such as Echinacea, green tea catechins and quadrivalent HPV vaccine, and their efficacy is yet to be completely established. Though some like levamisole have shown no efficacy as monotherapy and are now used only in combination, other more recent agents require large and long term randomized placebo-controlled trials to clearly establish their efficacy or lack of it. In this review, we focus on the immunomodulators that have been used for the treatment of warts and the studies that have been conducted on them.